The Role of Digital Libraries in Preservation of Regional Culture and Tradition - Mazurek, Cezary; Parkoła, Tomasz; Werla, Marcin (Studia Oeconomica Posnaniensia, 2013)
In the article we present the stages of building of Polish digital libraries infrastructure and the role of local and regional digital resources at the national and European level. The first chapter presents the most important issues related to online access of cultural heritage. In the second chapter we present crucial stages of the development of the Polish digital libraries network. Third chapter presents the idea and mission of the Digital Libraries Federation. The fourth chapter describes Polish digital libraries in the European context, focusing on matters related to local and regional digital resources and its location in the Europeana information space. The last chapter acts as a summary.